Status funcional e aspectos relacionados às condições de saúde de mulheres com artrite reumatoide em uso de drogas sintéticas modificadoras da doença: estudo observacional - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Chronic diseases begin and evolve slowly. They often present with varying symptoms, leading to complex health conditions. So it is with Rheumatoid Arthritis (RA), an inflammatory, autoimmune, systemic, chronic and progressive disease. It is more prevalent in women, in whom it presents a lower age of onset, a lower percentage of autoantibody positivity, more pain and worse functional capacity, suggesting a greater activity of the disease. Knowing the health conditions of a specific population can help health professionals to develop a plan of care focused on the person and not just on the disease. Objective: To characterize the functional status and some aspects of the health conditions of a specific group of adult women with RA. Method: Observational, cross-sectional study. Adult women with a diagnosis of RA (less than 17 years old), non-smokers, without previous lung disease, using synthetic DMARDs, without ever having used biological DMARDs, were studied. To characterize the sample, we used descriptive statistics with absolute (N) and relative (%) frequencies. Continuous numerical variables were presented as mean ± standard deviation (SD), median, maximum and minimum; categorical variables as absolute and relative frequencies. Fisher's exact test was used to test the dependence of two nominal categorical variables. The Variance-One-Way analysis model (ANOVA) was used to verify if there were differences between the means of a given variable (response variable) in relation to a predictor variable. Pearson's correlation coefficient was used to evaluate the degree of relationship between two quantitative variables. The level of significance was set at 0.05. Results: A total of 44 women with RA with early onset (diagnosis less than 40 years of age), with a mean illness duration of 9.9 (± 4.69) years, mean age 48 (± 7.98) years , most with normal functional status. The most sedentary, with low physical fitness (7.45 ± 0.816 METs), overweight, moderate pain level and reduced quality of life (worse scores in the environment and physical domains). Conclusion: Adult women with AR using synthetic DMARDs studied had compromised health conditions in a multidimensional manner. The presence of these conditions per se represent important points that can guide a better care and favor the better quality of life of these women. Keywords: Rheumatoid Arthritis; Classification; Complications; Health conditions.
Keywords: Artrite reumatoide; Classificação; Complicações; Condições de saúde; CIÊNCIAS DA SAÚDE: MEDICINA